Struktur Komunitas Mikrofita Sungai Pelus Kabupaten Banyumas Kaitannya dengan Kandungan Nutrien (Nitrat, Orthofosfat dan Silika) - Nur Laila Rahayu; Agatha Sih Piranti; Carmudi (UNU Purwokerto, 2021)
The increase in nutrients (nitrate, orthophosphate, and silica) will affect the microphytes as primary producers in the Pelus River ecosystem. This research aims to study NO3, PO4, Si(OH)4 concentration, the community structure of planktonic and benthic microphytes, and also the correlation between NO3, PO4, Si(OH)4 concentration with the benthic microphytes abundance in the Pelus River. The method used for this research was a survey method. Data were analyzed by calculating the community structure of planktonic and benthic microphytes, while quantitative analysis used indexes. The correlation between nitrate, orthophosphate, and silica concentrations was analyzed by multiple regression. The results showed that the composition of planktonic microphytes consisted of 34 species with an abundance of 41,637 ind.l-1, while benthic microphytes consisted of 54 species with an abundance of 89,908 ind.cm-2. The benthic microphytes community had moderate diversity (H'=1.50-2.58) and no dominant species (C=0.11-0.35). Individuals between species were not evenly distributed in each station (E=0.40-0.44). The correlation between nitrate, orthophosphate, silica concentration with the benthic microphytes abundance was very tight (r=0.999). The determination coefficient R2=0.998 indicated that the benthic microphytes abundance was influenced 99.8% by nutrient concentration. The remaining 0,2% was influenced by other factors such as current velocity and light penetration.